Crise hídrica e cafeicultura: impactos, resiliência e restrição de liberdade - o caso de Jaguaré/ES - Leffler, Ronaldo (2019)
It investigates the strategies of resilience to water crises adopted by coffee growers in the municipality of Jaguaré-ES, given the recurrence and magnitude of droughts in the largest coffee conilon producer in Brazil. Its objective is to present the main local impacts caused by the 2014-2017 water crisis in coffee plantations, as well as to characterize farmers' perception of droughts and their vulnerabilities; identify the resilience strategies developed by coffee growers and local institutions supporting coffee cultivation; and to propose local policies and actions aimed at the sustainable agricultural development of the municipality, based on the strategies (or not) of local coffee growers. This is a qualitative research, in which 182 coffee growers from the various land stratifications and regions of the municipality were interviewed and 21 key actors; 14 local and 7 other representatives of the state and federal executive power. The research is based on Amartya Sen's approach to empowerment, which defines development as the expansion of individual liberties. The results confirm the hypothesis of coffee farmers vulnerability to water crises, provoking economic, social and environmental impacts. Through the analysis of the perception of coffee growers, it can be said that they are aware of their vulnerabilities. The main strategies of resilience adopted by coffee growers were: localized irrigation; construction of dams and abstraction of groundwater; diversification of cultures and activities; Use and refinancing of agricultural credit. Public policies offered to coffee growers include the Legal Dam, Terra Viva and Agromais Program. It is concluded that there should be greater participation of coffee growers in trade unions, cooperatives and associations; development of public policies for technical assistance to coffee growers; study and control of the use of underground water resources in the region; processing, adding value to coffee, generating employment, income, expanding freedoms and improving the quality of life of coffee growers